Assessment of the Body Radioactivity of I-131 Using Two Techniques - Al-Musawi , Thaer Laftah (Iraqi Journal of Science, 2023)
Iodine-131 has become an essential radionuclide used in nuclear medicine for clinical and research purposes. The increase use of this radionuclide in medicine for diagnostic and treatment of thyroid diseases creates a demand to obtain a feasible methodology for occupational or accidental monitoring of internal contamination. In this study, two techniques were employed to find an appropriate one of in vivo bioassay for evaluating Iodine-131 body content. A scanning Whole Body Counter (WBC) equipped with 6NaI (Tl) scintillation detector, an anthropomorphic phantom and point source were used. The results showed that the counter sensitivity, as a first approach (conventional method), had a logarithmic and significant correlation with neck weight. On the other hand, the counting rate in the Compton band was considered, which is a measure of gamma ray attenuation, and found to have a direct relationship with body weight. The new technique, which is considered the variation of the counter sensitivity with the Compton to photopeak counting rate ratio, had the same regression but less uncertainty than the conventional approach. Finally, the theoretical MDA with neck weight was calculated for all the phantom configurations.